Regioselective Synthesis of Quinazolinone‐/Phenanthridine‐Fused Heteropolycycles by Pd‐Catalyzed Direct Intramolecular Aerobic Oxidative C−H Amination from Aromatic Strained Amides. Issue 10 (2nd February 2016) - Banerji, Biswadip; Bera, Suvankar; Chatterjee, Satadru; Killi, Sunil Kumar; Adhikary, Saswati
Abstract: A new route for the expedient synthesis of specific regioisomer of quinazolinone‐ and phenanthridine‐fused heterocycles through a palladium‐catalyzed regioselective intramolecular oxidative C−H amination from cyclic strained amides of aromatic amido–amidine systems (quinazolinones) has been developed. The amine functionalization of an aromatic C−H bond from a strained amide nitrogen involved in aromaticity has been a challenging work so far. The fusion of two heterocyclic cores, quinazolinone and phenanthridine, can occur in two different ways (linear and angular), but under the conditions reported here, only linear type isomer is exclusively produced. This approach provides a variety of substituted quinazolinone‐ and phenanthridine‐fused derivatives in moderate to excellent yields. Moreover, such fused molecules show excellent fluorescent properties and have great potential to be a new type of fluorophores for the use in medicinal and material science. Abstract : Fused rings : A novel approach to construct quinazolinone‐ and phenanthridine‐fused pentacyclic compounds has been developed efficiently by a regioselective palladium‐catalyzed C−H bond activation followed by an intramolecular amination of 2‐biphenyl‐2‐yl‐3H‐quinazolin‐4‐ones.